Pengaruh Art Therapy (Painting) dengan Media Tote Bag terhadap Self Efficacy pada Pasien Skizofrenia di RSJD Dr. Amino Gondohutomo Provinsi Jawa Tengah - Ersinidya, Ersinidya; Wahyuni, Endang Sri (Jurnal Terapi Wicara dan Bahasa, 2024)
Abstract Background: Schizophrenia is a group of psychotic symptoms that affect different areas of the functioning of a person. Schizophrenics will experience impaired social functioning that is influenced by self-efficacy. Self-efficacy is a very important motivating factor to achieve success. One of the non-pharmacological therapies that can be given is art therapy (painting).  Objectives: This study was used to determine the effect of art therapy (painting) with tote bag media on self-efficacy in schizophrenia patients at RSJD Dr. Amino Gondohutomo Province of Central Java. Methods: This research is a pre-experimental quantitative research with one group pre and post-test design. The sampling technique uses purposive sampling with a population of 35 samples. Self-efficacy was measured using the Indonesian version of the General Self-Efficacy Scale (GSES) instrument. Hypothesis testing uses the Wilcoxon test. Results: The results showed that the age was predominantly late adulthood (45.7%), the majority were female (65.7%), the work history was predominantly non-working (37.1%), the majority of the sample had a marital status of being unmarried (60.0%), education level was dominated by SMA/MAN/SMK (42.9%), and the majority of the sample had an unspecified diagnosis of schizophrenia (65.7%). The average pre-test score is 21.91 and the post-test score is 29.89 with a difference of 7.98, which means there are differences in the results of the self-efficacy examination in the research sample. The results of this research were measured using the Wilcoxon test, obtaining a p-value of 0.000 (p-value <0.05). Conclusion Activities of art therapy (painting) with tote bag media influence self-efficacy in schizophrenia patients at RSJD Dr. Amino Gondohutomo Province of Central Java. It is hoped that the results of this research can become a routine therapeutic activity for schizophrenia patients at RSJD Dr. Amino Gondohutomo Province of Central Java. Keywords : Art Therapy (Painting), Self Efficacy, Schizophrenia